A story of identity: a cautionary tale. (June 2017) - Lewis, Patrick J
This is a personal narrative drawing upon the multi-dimensionality of narrative and storytelling to make sense of lived-experience. The article is an experience that deals with Indigenous Identity fraud in the academy in the moment of Reconciliation with Indigenous People and the people of Canada. It is a story of White settler claims to being Indigenous so as to reposition themselves within university discourse of Indigenisation. The narrative weaves through the structures and practices of colonisation, the complexities of identity and racialisation, and the restraint of universities to take up Indigenisation in a meaningful and authentic way. A restraint that may actually contribute to the continued erasure of Indigeneity.